An evaluation of ultra low volume inseticide sprays application for dengue control in areas of Hortolândia e Sumaré municipalities, SP, Brazil - Caporalle Mayo, Renata; Andrade, Valmir Roberto Andrade; Ferreira Leite, Odair; Luna Castor de Lima, Virgília (BEPA. Boletim Epidemiológico Paulista, 2011)
The 2006/2007 dengue epidemic was the greatest in São Paulo state until those years. Hortolândia and Sumaré municipalities showed high transmission levels. The Institution that coordinate the state control Program, SUCEN, organized especial teams for domiciliary space ultra low volume sprays application to reduce quickly the adult vectors population and consequently help municipalities staff to interrupt transmission in higher transmission areas. The municipality teams work mainly removing the recipients serving as vectors breeding sites. The aim of this paper is to evaluate these SUCEN especial teams control activities. It is a descriptive study where vector infestation levels are compared before and after. Number of dengue confirmed cases is also compared. In Sumaré, it was done a survey inquiring residents, in the study area, about the insecticide application. It was observed an intense reduction in ovitramp positivity and egg density in the week after control activity. Though, in next week ovitramp positivity and egg density values were higher. It was not possible to determine the effect of these special team domiciliary space ultra low sprays application in reducing the number of dengue cases because when it began the case number was already descendent. The activity was well evaluated and well accepted by the people living in the area. The conclusion is that is necessary to remove hardly the breeding sites, before the activity and in the weeks after it, associated with health education, to maintain low infestation levels.